Epidemiology of invasive group A Streptococcus infections in Sydney, Australia. Issue 4 (June 2015) - Sivagnanam, Shobini; Zhou, Fei; Lee, Andie S.; O'Sullivan, Matthew V. N.
<x xml:space="preserve">Abstract</x> Summary There is concern of global resurgence of invasive group A Streptococcus (iGAS) infections. We compared the clinical and molecular epidemiology of patients admitted with iGAS over two time periods, 2008 and 2010, in Western Sydney, Australia. The annual incidence was 19 cases per 100, 000 admissions in 2008, compared to 33 per 100, 000 in 2010. An increasing proportion of patients died (0% versus 13%), had an APACHE II score ≥30 (0% versus 19%), and had no known risk-factors (12% versus 25%). A potential skin source was identified as a trigger in fewer cases in 2010 (36% versus 11%). In total, there were 27 different emm types and 11 different emm clusters. There were some new emm types/clusters in 2010 that were not present in 2008. However, the study was not adequately powered to detect statistically significant differences in the distribution of emm types (p = 0.06) and emm clusters (p = 0.16) between the two years. There were also no clear associations between emm types/clusters and severity and clinical manifestations of iGAS infections. Although the proposed 30-valent M protein vaccine encompasses only 47% of our isolates, it will likely provide coverage for at least 71% of iGAS infections due to cross-opsonisation.